Introduction To The Special Issue On The Psychodynamic Diagnostic Manual, 2nd Edition (Pdm-2): The Pdm: Yesterday, Today, Tomorrow - Lingiard, Vittorio; Mcwilliams, Nancy (Զանգակ հրատ.)
In this introductory essay, we review the development of the second edition of the Psychodynamic Diagnostic Manual. We place the first edition in historical context and note the main responses and critiques of professional colleagues to its publication. We then outline the developing process of this second, comprehensively revised edition. Finally, we preview the contributions to this Special Issue. Overall, we emphasize the Psychodynamic Diagnostic Manual’s innovative diagnostic framework, designed to assess the depth as well as the surface of patients’ emotional, cognitive, interpersonal, and social patterns and to foster in the field an integration between nomothetic understanding and the idiographic knowledge useful for case formulation and treatment planning.
Keywords: Psychology